AN INVESTIGATION OF PROSPECTIVE TEACHERS’ 21ST CENTURY SKILLS EFFECT ABOUT DIGITAL STORYTELLING EVENTS - Kaya, Vildan Donmuş; Akpunar, Bürhan (My University, 2018)
The aim of the study was to investigate prospective teachers' views about digital storytelling event onthe effect of 21st century skills. This study was designed with descriptive models. The sample wasselected by using appropriate sampling of non-random sampling method. 58 prospective teachers (31female and 27 male) who study at Fırat University Faculty of Sport Science in first semesterparticipated in this study. Prospective teachers from instructional technology and material designcourse were wanted create \"digital stories\". Following the steps necessary for prospective teachers tocreate a digital story process has been completed. Data was collected in the first half of 2015- 2016academic year through 21st century skills survey (21CSS) (Karakoyun, 2014). Cronbach's alphacoefficient survey consists of 41 items about 21CSS is originally calculated as 0.96 but it wascalculated as 0.98 in this study. There are three Sub-Dimensions in 21CSS which are learning andinnovation skills (B1), information, media and technology skills (B2), life and professional skills(B3). Data was analyzed by descriptive statistics, t-test and ANOVA.According to the findings, mean based on the teachers' candidates of physical education towards thelearning and innovation skills 3.33; mean based on the information, the media and technology skills3,86; mean based on the life and professional skills 3,94; mean based on the total score of 21CSS (T)was calculated as the 3.86. According to variable of gender, the prospective teachers’ scores aboutB1, B2, B3 and T has been found no effect. However, it is observed that female prospectiveteachers’ mean scores were higher than mean score of male teachers about all of Sub-Dimensions.According to level of internet usage, the prospective teachers’ scores about B1, B2, B3 and T hasbeen found no effect. According to level of computer usage, the prospective teachers’ scores aboutB1, B2, B3 and T has been found no effect.
Keywords: Eğitim; Eğitim Araştırmaları